Geological Modeling of Hydrocarbon Reservoir Rocks in the Mafia Basin, Offshore Tanzania - Mohamed, Bahati; Mshiu , Elisante; Mulaya, Ernest (Tanzania Journal of Science, 2021)
This study presents a 3D geological model of reservoir rocks in the Mafia Basin based on interpretation of 2D seismic and well data towards understanding the hydrocarbon prospectivity. 2D seismic data were used to generate surface maps and therefore the subsurface configuration of the reservoir complemented with petrophysical analysis to determine lithology and reservoir properties. Structural and petrophysical properties modeling were distributed stochastically within the constructed 3D grid using Sequential Indicator Simulation (SIS) and Gaussian Random Function Simulation (GRFS) algorithms. Results from well log analysis and petrophysical models classify the reservoir under a moderate reservoir quality with 19% to 20% porosity, 6–7 mD permeability and 60% to 65% water saturation. The observed high values of water saturation imply that the hydrocarbon accumulation in the mapped area is insignificant. The reservoir structural model and subsurface configuration shows stratigraphical trap as the only trapping mechanism in the area.. However, 3D seismic and multiple wells are needed for effective correlation of geological information to enhance the structural configuration and lateral continuity of the reservoir. Keywords: Geological modeling; Mafia basin; 2D seismic data; reservoir rocks